Effect of Work Compensation and Discipline on Employee Performance in PT. Berjaya Group Medan - Sondang Ni Bulan Marbun; Donna Maryati Panggabean (Britain International for Academic Research (BIAR) Publisher, 2020)
The purpose of this study was to analyze and determine the extent of the effect of compensation and work discipline on employee performance at PT. Berjaya Group Medan. Through a descriptive method involving 84 respondents, data was collected using a questionnaire. Data processing is done by SPSS using multiple regression analysis. The results show that compensation and work discipline have a regression coefficient which proves the relationship between compensation and discipline on performance at PT. Berjaya Group Medan.